Reduced gamma oscillations in a mouse model of intellectual disability: a role for impaired repetitive neurotransmission? - Powell, Andrew D; Saintot, Pierre-Philippe; Gill, Kalbinder K; Bharathan, Ashtami; Buck, S Caroline; Morris, Gareth; Jiruska, Premysl; Jefferys, John G R (PloS one, 2014)
Intellectual disability affects 2-3% of the population; mutations of the X-chromosome are a major cause of moderate to severe cases. The link between the molecular consequences of the mutation and impaired cognitive function remains unclear. Loss of function mutations of oligophrenin-1 (OPHN1) disrupt Rho-GTPase signalling. Here we demonstrate abnormal neurotransmission at CA3 synapses in hippocampal slices from Ophn1-/y mice, resulting from a substantial decrease in the readily releasable pool of vesicles. As a result, synaptic transmission fails at high frequencies required for oscillations associated with cognitive functions. Both spontaneous and KA-induced gamma oscillations were reduced in Ophn1-/y hippocampal slices. Spontaneous oscillations were rapidly rescued by inhibition of the downstream signalling pathway of oligophrenin-1. These findings suggest that the intellectual disability due to mutations of oligophrenin-1 results from a synaptopathy and consequent network malfunction, providing a plausible mechanism for the learning disabilities. Furthermore, they raise the prospect of drug treatments for affected individuals.
Keywords: jaderné proteiny; nervový přenos; hipokampální oblast CA3; Nuclear Proteins; Intellectual Disability; myši inbrední C57BL; mentální retardace; Mice; proteiny aktivující GTPasu; zvířata; Cytoskeletal Proteins; GTPase-Activating Proteins; cytoskeletální proteiny; Synaptic Transmission; myši; Gamma Rhythm; CA3 Region, Hippocampal; gama rytmus EEG; Mice, Inbred C57BL; Animals